Creating a technical architecture framework for m-voting application. Issue 1 (2nd January 2022) - Iyamu, Tiko
Abstract : South Africa's general election of 2019 posed many challenges, some of which threatened the credibility of its result, and the entire election process. Some of the challenges were multiple voting, many hours of queuing, which led to fatigue, and a significant decline in the number of voters owing to the limited timeframe. These factors heighten the need for m-voting as an alternative or complementary method of voting in the country. Owing to similar challenges, many studies have been conducted, which consequently focused on development and strengthening of security features of e-voting and m-voting applications. However, many countries, including South Africa are not deploying the applications because of their complex nature, such as not being able to trace and track its components. The complexity is attributed to the lack of an architecture framework. This paper presents a technical architecture framework, to support and guide the development and implementation of m-voting applications, to possibly eradicate complexity and enhance the electoral process in South Africa. The outcome of this study was based on findings from analysis of existing materials and semi-structured interviews, in which the hermeneutics approach was employed.